ANALISIS PENERIMAAN PAJAK HOTEL DAN PAJAK RESTORAN PADA BADAN PENDAPATAN DAERAH DI KOTA MEDAN - Syahril, Syahril; Sanjaya, Surya; Amelia, T. Nurul Rizky (CERED Indonesia Institute, 2026)
. The research method used is a descriptive method, the type of data used is quantitative, the data technique is carried out using documentation techniques to analyze using three methods, namely effectiveness level analysis, contribution analysis and growth rate analysis. This research took place at the Medan City Regional Revenue Service (Dispenda) Office. The results of this research show that the Regional Revenue Service (Dispenda) has prepared the regional original revenue budget well. Researchers draw the conclusion that from 2018 to 2022, the growth in the number of businesses in hotel taxes and restaurant taxes is quite stable, namely around 14% -29%. However, in 2020, the growth in the number of hotel and restaurant businesses in Medan City decreased quite drastically, hotel tax growth was -53.60% and restaurant tax growth was -34.02%. The hotel tax and restaurant tax revenues that have met the criteria are quite successful in their level of effectiveness, where the average level of effectiveness for hotel taxes is 81.92% and for restaurant taxes is 87.66%. Meanwhile, the average contribution to hotel tax is 5.57% and to restaurant tax 11.56%.